7 Lateral Canthal Eyelid Reconstruction (Eyelid Reconstruction, 2020)
The lateral canthus is not as anatomically complex as the medial canthus; nonetheless, this region is of major importance to facial cosmesis and ocular health. Incorrect reconstruction at the lateral can-thus can lead to postoperative ectropion, tearing, and eye pain. The techniques presented in this chapter will offer reconstructive options to enable the surgeon to achieve the goal of reconstructing the outer eyelid area for optimal functional and cosmetic result.
Keywords: lateral canthus; Mohs reconstruction; Tenzel; Mustarde; advancement; periosteal flap; Fricke; Tripier